Influence of short-term binder-bentonite interactions on workability of sand-bentonite-binder mixture for seepage cut-off wall - Ting, Matthew Zhi Yeon (2023)
Bentonite is commonly used as sealing material in seepage cut-off walls to minimize the permeability of sandy soil. To further reduce permeability and stabilize the sand-bentonite mixture, binders such as ordinary Portland cement (OPC) can be added. However, OPC can interact with bentonite and cause cation exchange, resulting in increased flowability and bleeding of soil mixture. Hence, this study proposes alternative bentonites and binders to reduce the influence of the short-term binder-bentonite interactions on the workability. The performance of three bentonite types, including sodium, calcium and salt-resistant bentonites, was evaluated. The use of ground granulated blastfurnace slag (GGBS) with activators of reactive magnesia (MgO) and quicklime (CaO) as alternative binders was also studied. When compared to OPC, MgO-GGBS had flowability of 1.7%–21.7% and bleeding of 0.6%–1.4% less, whereas CaO-GGBS had flowability of 1.9%–3.7% and bleeding of 0.1%–1.6% more. Mg2+ ions from MgO-GGBS had a lower affinity to participate in cation exchange with bentonite than Ca2+ ions from OPC and CaO-GGBS. The flowability and bleeding decreased further by 0.7%–5.4% and 6.2%–30.3%, respectively, when MgO reactivity and content increased. Besides, the binder-bentonite interactions had the least influence on salt-resistant bentonite, followed by calcium bentonite and then sodium bentonite, due to its low exchangeable sodium content. The XRD analysis also revealed that the short-term interactions of binder with bentonite tended to convert Na-based montmorillonite to Ca-based montmorillonite. In summary, the use of MgO-GGBS and salt-resistant bentonite can minimize the binder-induced cation exchange effect on the workability of sand-bentonite-binder mixture in cut-off wall construction.